Replacing, reducing and refining the use of animals in tuberculosis vaccine 1 research - Tanner, R; McShane, H (ALTEX Edition, 2016)
Tuberculosis (TB) remains a serious global health threat and an improved vaccine is urgently needed. New candidate TB vaccines are tested using preclinical animal models such as mice, guinea pigs, cattle and non-human primates. Animals are routinely infected with virulent Mycobacterium tuberculosis (M.tb) in challenge experiments to evaluate protective efficacy, raising ethical issues regarding the procedure of infection itself, symptoms of disease and humane end-points. We summarise the importance and limitations of animal models in TB vaccine research and review current alternatives and modifications in the context of the NC3Rs framework for replacing, reducing and refining the use of animals for scientific purposes.